Narratives and songs in Karimojong oral literature - Aloka, Aloysius, 1961- (Kampala : Makerere University, 1992)
Thesis (M.A) Literature - Makerere University, 1992.
Includes bibliographical references (p.182-183)
Keywords: Folk literature -- Karimojong -- Uganda